An efficient flame retardant for epoxy resin: Preparation and pyrolytic behaviour. (November 2019) - Yang, Baoping; Li, Xiang; Wang, Lurong; Zhang, Yabin; Cui, Jinfeng; Guo, Junhong; Tian, Li
Using 4, 4-diaminodiphenyl methane as a curing agent, three kinds of monomers, 4, 4′-dihydroxybenzophenone, diphenyl chlorophosphite and 1, 4-phenylene diisocyanate (NCO), were introduced into a thermosetting resin (DGEBA). The flame retardancy properties of the composites were studied, and the results were compared with those of 5 wt% bis(bis(4-((diphenoxyphosphoryl)oxy)phenyl)methyl) 1, 4-phenylenedicarbamate (DHPP-OH-NCO), 10 wt% DHPP-OH-NCO and 15 wt% DHPP-OH-NCO curing agents. The results showed that 15 wt% DHPP-OH-NCO had an improved flame retardancy, the limited oxygen index reached 33.5% and the vertical burning test (UL94) achieved a V-0 level. A cone calorimeter experiment showed that the addition of the flame retardant significantly reduced the amount of generated smoke and heat. Macroscopic digital images, scanning electron microscopy images and thermogravimetric analysis results further revealed that the epoxy resin (EP) with DHPP-OH-NCO exhibited greater char yields. The flame retardancy mechanism of the flame retardant was preliminarily shown by pyrolysis–gas chromatography–mass spectrometry analysis. The combined test results demonstrate that a high-efficiency phosphorous-containing flame retardant for EPs was successfully developed.